Effectiveness of Cooperation in Virtual Teams - Editha Dewi Purnamasari; Saimarlina Harahap; Rina Irawan; Apriliana Fajri Wibowo (Bulletin of Computer Science and Electrical Engineering, 2022)
Technological development has led to the emergence of cooperation separately both geographically and in time zone in an organization in the form of a virtual organization. PT XYZ's Microsoft Solution and Service (DMSS) Department is one of the departments that provides digital services in the form of One-Stop-Solutions on Digital Services, both in on-premise and cloud infrastructure models with products and solutions based on Microsoft products for customers. In his service during the Covid-19 pandemic, this department implements virtual team coordination so that product development can continue as planned. However, on the other hand, the effectiveness of performance in implementing virtual organizations is still a challenge for the company. This is the focus of research to find out what factors influence the effectiveness of cooperation in the application of virtual organizations at PT XYZ in general and specifically in the Microsoft Solution and Service Department. This study conducted an analysis of seven factors by surveying 40 respondents at PT. XYZ. The results obtained are three factors consisting of depth of communication, technology, and training which have an influence on the effectiveness of the application of virtual organizations at PT. XYZ, while four other factors such as trust, shared understanding of knowledge, commitment, and leadership have no significant effect on the effectiveness of virtual organizations.